2009
DOI: 10.1007/s12032-009-9329-2
|View full text |Cite
|
Sign up to set email alerts
|

VEGF −460C>T polymorphism and cancer risk: a meta-analysis

Abstract: Vascular endothelial growth factor (VEGF) is a major driver of physiological and pathological angiogenesis and plays important roles in the etiology and metastasis of cancers. The -460C>T polymorphism in VEGF gene region has been implicated in cancer risk and related to VEGF expression. However, published data remain conflicting. To derive a more precise estimation, a meta-analysis of 5,863 cases and 5,276 controls from 14 published case-control studies was performed. Odds ratios (ORs) with 95% confidence inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The previous metaanalyses performed by Xu et al, 35 Hong et al, 36 and Liu et al 37 contained one study related to OC; those by Cao et al 38 and Hong et al 39 included 2 studies that tested OC. None of these 5 meta-analyses focused exclusively on OC, and none of them conducted subgroup analysis for OC.…”
Section: Discussionmentioning
confidence: 99%
“…The previous metaanalyses performed by Xu et al, 35 Hong et al, 36 and Liu et al 37 contained one study related to OC; those by Cao et al 38 and Hong et al 39 included 2 studies that tested OC. None of these 5 meta-analyses focused exclusively on OC, and none of them conducted subgroup analysis for OC.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF gene -460T/C polymorphism, one of the most frequently seen polymorphisms, is located at the -460 position in the promoter region. VEGF gene promoter region contains multiple regulatory elements, which involved in the regulation of VEGF gene expression, and -460T/C polymorphism C allele showed 70% increased promoter activity over T allele [36,37]. Therefore, we speculate that -460T/C polymorphism may increase expression of VEGF , resulting in a increased susceptibility to DR. Of course, the detailed mechanisms need further study.…”
Section: Discussionmentioning
confidence: 99%
“…There might be some other SNPs in VEGF associated with risk of cancer. Xu et al [24] conducted a meta-analysis of 14 studies showed the evidence that VEGF -460T was associated with increased cancer risk in Asians. Schneider et al [25] found that VEGF -1498C alleles contributed to the susceptibility of breast cancer in American population.…”
Section: Discussionmentioning
confidence: 99%